Rhodiola rosea root extract has antipsychotic-like effects in rodent models of sensorimotor gating. (10th May 2019) - Coors, Andreas; Brosch, Marcel; Kahl, Evelyn; Khalil, Radwa; Michels, Birgit; Laub, Annegret; Franke, Katrin; Gerber, Bertram; Fendt, Markus
Abstract: Ethnopharmacological relevance: The plant arctic root (Rhodiola rosea, L . ) is growing in northern regions of Europe, Asia and North America. Extracts of R. rosea are used in traditional medicine for various conditions related to nervous system function. According to scientific studies from the last decades, the plant might have potential for use in the treatment of memory impairments, stress and depression, but reports concerning other neuropsychiatric disorders are scarce. Aim of the study: In this context, our study aimed to examine potential antipsychotic-like effects of R. rosea root extract. Materials and methods: We tested the effects of R. rosea root extract on prepulse inhibition in rats and mice. Prepulse inhibition is an established operational measure of sensorimotor gating, which is impaired in schizophrenia and other psychotic disorders. Results: R. rosea root extract increased prepulse inhibition in rats and mice. Interestingly, the R. rosea extract had stronger effects in those individual animals that had low baseline levels of prepulse inhibition. Therefore, we performed further experiments in which we pharmacologically induced a prepulse inhibition deficit by two different psychostimulants, either the dopamine D2 receptor agonist apomorphine or the NMDA receptor antagonist dizocilpine (MK-801). Pre-treatment with the R. rosea extract significantly restored both, apomorphine- and dizocilpine-induced prepulse inhibition deficits. Conclusions: The present study demonstrates that R. rosea extract robustly reverses prepulse inhibition deficits in rodents. This suggests antipsychotic-like effects of R. rosea extract. Future studies should focus on the pharmacological mechanisms underlying these effects. Graphical abstract: fx1